Respuesta :
y=a(x-h)^2+k using the vetex (1,-9) for (h,k)
y=a(x-1)^2-9 and we are given the point (0,-6)
-6=a(-1)^2-9
-6=a-9
3=a
y=3(x-1)^2-9
The x-intercepts occur when y=0 so
3(x-1)^2-9=0 divide both sides by 3
(x-1)^2-3=0
(x-1)^2=3
x-1=±√3
x=1±√3
So the intercepts are the points:
(1+√3, 0) and (1-√3, 0)
y=a(x-1)^2-9 and we are given the point (0,-6)
-6=a(-1)^2-9
-6=a-9
3=a
y=3(x-1)^2-9
The x-intercepts occur when y=0 so
3(x-1)^2-9=0 divide both sides by 3
(x-1)^2-3=0
(x-1)^2=3
x-1=±√3
x=1±√3
So the intercepts are the points:
(1+√3, 0) and (1-√3, 0)
The x-intercepts of the parabola with vertex (1,-9) and y-intercept of (0,-6) are of [tex]x = 1 \pm \sqrt{3}[/tex].
What is the equation of a parabola given it’s vertex?
The equation of a quadratic function, of vertex (h,k), is given by:
y = a(x - h)² + k
In which a is the leading coefficient.
In this problem, the parabola has vertex (1,-9), hence h = 1, k = -9, and:
y = a(x - 1)^2 - 9.
The y-intercept is of (0,-6), hence when x = 0, y = -6, and this is used to find a.
-6 = a - 9
a = 3.
So the equation is:
y = 3(x - 1)^2 - 9.
y = 3x² - 6x - 6.
The x-intercepts are the values of x for which:
3x² - 6x - 6 = 0.
Then:
x² - 2x - 2 = 0.
Which has coefficients a = 1, b = -2, c = -2, hence:
[tex]\Delta = b^2 - 4ac = (-2)^2 - 4(1)(-2) = 12[/tex]
[tex]x_1 = \frac{2 + \sqrt{12}}{2} = 1 + \sqrt{3}[/tex]
[tex]x_2 = \frac{2 - \sqrt{12}}{2} = 1 - \sqrt{3}[/tex]
The x-intercepts of the parabola are [tex]x = 1 \pm \sqrt{3}[/tex].
More can be learned about quadratic equations at https://brainly.com/question/24737967
#SPJ2